2017
DOI: 10.1007/s11745-017-4257-y
|View full text |Cite
|
Sign up to set email alerts
|

Dietary PUFA Increase Apoptosis in Stomach of Patients with Dyspeptic Symptoms and Infected with H. pylori

Abstract: Drug-resistant strains of Helicobacter pylori and poor treatment response are the main reasons for the failure in eradicating it in patients. Polyunsaturated fatty acids (PUFA) have an inhibitory effect on bacterial growth. The aim of this study was to investigate the effect of PUFA in combination with standard triple therapy on apoptosis in H. pylori infected subjects with dyspeptic symptoms. This study was a double-blind clinical trial in which 34 H. pylori infected subjects with dyspeptic symptoms were rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…According to studies, the association of oxidative stress with cancer has been confirmed [2]. In other words, oxidative stress is created as a result of disturbance between the production of free radicals (active oxygen and nitrogen species) and the antioxidant defense system [3]. In aerobic biological systems, superoxide dismutase enzymes (SOD), glutathione peroxidase (GPX), catalase and vitamins are important in controlling free radicals [4].…”
Section: Introductionmentioning
confidence: 99%
“…According to studies, the association of oxidative stress with cancer has been confirmed [2]. In other words, oxidative stress is created as a result of disturbance between the production of free radicals (active oxygen and nitrogen species) and the antioxidant defense system [3]. In aerobic biological systems, superoxide dismutase enzymes (SOD), glutathione peroxidase (GPX), catalase and vitamins are important in controlling free radicals [4].…”
Section: Introductionmentioning
confidence: 99%